Exploring the Use of PMS in a New Hotel: A Case Study in Nio Garden Hotel Sumbawa - Kevin Gustian Yulius; Kezia Evelyn (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: This study investigates how the implementation of a Property Management System at Nio Garden Hotel Sumbawa influences the efficiency of Front Office operations and the overall quality of guest service. It seeks to understand the extent to which early adoption of a digital management platform can support a new hotel in a developing tourism region. Research methods: A qualitative case study approach was employed. Primary data were gathered through a semi structured interview with the Front Office Manager. Secondary data comprised a thematic analysis of twenty nine guest reviews sourced from Google Review, Booking.com, Tiket.com, and Agoda.com. The property management system under study is Atlantis. Results and discussion: The system has improved the speed and accuracy of reservation handling, check in and check out procedures, billing, and room status management. Nevertheless, challenges persist in the assignment of rooms under maintenance, uneven integration of payment methods in the restaurant, and lapses in communication that affect breakfast availability and guest notifications. These findings indicate that while the system has potential, full optimization is hindered by staff learning curves and partial deployment of key features. Implication: To maximize the benefits of a property management system in small or family-owned hotels, continuous staff training, deeper integration across all hotel departments, and proactive digital communication strategies are essential. This will lead to more consistent service delivery and higher levels of guest satisfaction.